Seismic Performance of Lightweight Concrete Structures - Swamy Nadh Vandanapu; Muthumani Krishnamurthy (Advances in Civil Engineering)
Concrete structures are prone to earthquake due to mass of the structures. The primary use of structural lightweight concrete (SLWC) is to reduce the dead load of a concrete structure, which allows the structural designer to reduce the size of the structural members like beam, column, and footings which results in reduction of earthquake forces on the structure. This paper attempts to predict the seismic response of a six-storied reinforced concrete frame with the use of lightweight concrete. A well-designed six-storey example is taken for study. The structure is modelled with standard software, and analysis is carried out with normal weight and lightweight concrete. Bending moments and shear forces are considered for both NWC and LWC, and it is observed that bending moments and shear forces are reduced to 15 and 20 percent, respectively, in LWC. The density difference observed was 28% lower when compared NWC to LWC. Assuming that the section and reinforcements are not revised due to use of LWC, one can expect large margin over and above MCE (maximum considered earthquake; IS 1893-2016), which is a desirable seismic resistance feature in important structures.